APPLICATION OF DIVERSION OF BULLYING CRIMES AGAINST CHILDREN WITH DISABILITIES - Komariah, Mamay; Haris, Abdul; Ismayana (Hukum Responsif, 2024)
Children are an inseparable part of the growth of a nation. Law Number 35 of 2014 concerning Child Protection. Objectives of the study: 1. To find out how the diversion of crimes committed by children is applied at the prosecutor's level. 2. To find out the obstacles law enforcement faces against child violence. Bullying occurred on September 19, 2022, in Bojong Village, Susukan District, Cirebon Regency. Three high school teenagers bullied people with disabilities whose news had gone viral on social media. In this case, the perpetrator was a minor, committing acts of violence against a child with disabilities by mocking and kicking the victim. Individual law enforcement that is not strong will result in crimes or criminal acts that result in people committing criminal acts due to ineffective law enforcement. This study uses an empirical juridical method, which is carried out on facts or events related to the problems in this thesis, using qualitative descriptive where the data obtained from both library studies and interviews will be analyzed by explaining and explaining the results of the research object, then describing the results of the research in the form of mapping the problem after the process will conclude. Based on the research, it can be concluded that the procedural implementation of Diversion efforts at the Cirebon District Attorney's Office has been under Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. However, it is not optimal in terms of substance. Of the 17 cases that entered the 2022-2023 period, 10 should have been able to be done, but only 5 cases were successfully pursued by the JPU. The inhibiting factors include weaknesses in Law No. 11 of 2012 SPPA and the community's mindset that considers settlement through Diversi detrimental to the victim.